Unity in numbers : the archaeology of the demimonde (1840-1917) - Sharpless, Megan (My University, 2008)
Prostitution served as a logical economic career choice for women in the nineteenth century due to a lack of prosperous labor options. It offered the hope of a modest economic status and autonomy for women despite the societal isolation, prejudices, and health risks associated with the trade. Recent archaeological excavations of brothels offer a more complete understanding of these working-class and marginalized women. Material evidence of their daily lives can further expand our knowledge in such areas and contextualize the narratives of historical analysis. A limited but growing field in historical contract archaeology of vice and Red-Light districts, in cities such as New York, Washington, D.C., New Orleans, and Los Angeles, can help explain various aspects of class, gender, and sexuality in this time period. The investigation and interpretation of the material record provides crucial evidence into the residences of these women. By taking a look at parallel and unparallel patterns and associations in artifact assemblages, a clearer understanding of what constitutes brothel material culture in the nineteenth century can be more clearly defined. The categories of my results included faunal remains, ceramics, pharmaceutical accoutrement, child-related artifacts, and personal items. The history and analysis of prostitution covers the oldest female labor trade in the world.
Keywords: Archaeological assemblages; Prostitution -- United States -- History -- 19th century; Brothels -- United States -- History -- 19th century